Impact of mechanical ventilation on severe acute kidney injury in critically ill patients with and without COVID-19 – a multicentre propensity matched analysis - Fabian Perschinka; Timo Mayerhöfer; Teresa Engelbrecht; Alexandra Graf; Paul Zajic; Philipp Metnitz; Michael Joannidis (Annals of Intensive Care)
Abstract Background Acute kidney injury (AKI) is common in critically ill patients and is associated with increased morbidity and mortality. Its complications often require renal replacement therapy (RRT). Invasive mechanical ventilation (IMV) and infections are considered risk factors for the occurrence of AKI. The use of IMV and non-invasive ventilation (NIV) has changed over the course of the pandemic. Concomitant with this change in treatment a reduction in the incidences of AKI and RRT was observed. We aimed to investigate the impact of IMV on RRT initiation by comparing critically ill patients with and without COVID-19. Furthermore, we wanted to investigate the rates and timing of RRT as well as the outcome of patients, who were treated with RRT. Results A total of 8,678 patients were included, of which 555 (12.8%) in the COVID-19 and 554 (12.8%) in the control group were treated with RRT. In the first week of ICU stay the COVID-19 patients showed a significantly lower probability for RRT initiation (day 1: p < 0.0001, day 2: p = 0.021). However, after day 7 a reversed HR was found. In mechanically ventilated patients the risk was significantly higher for the initiation of RRT over the entire stay. While in non-COVID-19 patients this was a non-significant trend, in COVID-19 patients the risk for RRT was significantly increased. The median delay between initiation of IMV and requirement of RRT was observed to be longer in COVID-19 patients (5 days [IQR: 2–11] vs. 2 days [IQR: 1–5]). The analysis restricted to patients with RRT showed a significantly higher risk for ICU death in patients requiring IMV compared to patients without IMV. Conclusion The analysis demonstrated that IMV as well as COVID-19 are associated with an increased risk for initiation of RRT. The association between IMV and risk of RRT initiation was given for all investigated time intervals. Additionally, COVID-19 patients showed an increased risk for RRT initiation during the entire ICU stay within patients admitted to an ICU due to respiratory disease. In COVID-19 patients treated with RRT, the risk of death was significantly higher compared to non-COVID-19 patients.